2023
DOI: 10.1111/1751-7915.14215
|View full text |Cite
|
Sign up to set email alerts
|

Production of selenium nanoparticles occurs through an interconnected pathway of sulphur metabolism and oxidative stress response in Pseudomonas putida KT2440

Abstract: The soil bacterium Pseudomonas putida KT2440 has been shown to produce selenium nanoparticles aerobically from selenite; however, the molecular actors involved in this process are unknown. Here, through a combination of genetic and analytical techniques, we report the first insights into selenite metabolism in this bacterium. Our results suggest that the reduction of selenite occurs through an interconnected metabolic network involving central metabolic reactions, sulphur metabolism, and the response to oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…It was shown that yll058w was identified as an upregulated gene in both the selenium and sulfur metabolism pathways. Due to the chemical similarity between selenium and sulfur, under sodium selenite stress, sodium selenite is reduced through an interconnected metabolic network that includes selenium metabolism, sulfur metabolism, and the oxidative stress response . Therefore, enzymes in the selenium and sulfur metabolism pathways, such as TRR and YLL058W, are involved in the reduction pathway of sodium selenite, with key genes (such as trr1 , trr2 , and yll058w ) showing upregulated expression to maintain cellular redox balance and enhance redox activity.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that yll058w was identified as an upregulated gene in both the selenium and sulfur metabolism pathways. Due to the chemical similarity between selenium and sulfur, under sodium selenite stress, sodium selenite is reduced through an interconnected metabolic network that includes selenium metabolism, sulfur metabolism, and the oxidative stress response . Therefore, enzymes in the selenium and sulfur metabolism pathways, such as TRR and YLL058W, are involved in the reduction pathway of sodium selenite, with key genes (such as trr1 , trr2 , and yll058w ) showing upregulated expression to maintain cellular redox balance and enhance redox activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an increasing number of studies have reported that Se­(IV) reduction functions as a detoxification mechanism in microorganisms. The reported Se­(IV) reduction pathways included a Painter-type reaction involving thiol groups, thioredoxin reductase system, siderophore-mediated reduction, sulfide-mediated reduction, and dissimilatory reduction. ,, Aerobic microorganisms can utilize electron donors such as thiol, sugars, hydrogen, NADP, and NADPH to reduce Se. The gene grx A encodes a glutathione-dependent reductase that can aerobically reduce Se­(IV) into SeNPs in the P. stutzeri strain TS44 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutations affecting the activity of the sulphite reductase decreased the bacteria's ability to transform selenite into Se(0). Interestingly, suppression of genes sqrR , sqr and pdo2 resulted in the production of selenium nanoparticles at a higher rate than the wild‐type strain, which is an observation of great biotechnological interest (Avendaño et al, 2023 ).…”
Section: Lessons From the Molecular Determinants Responsible For ...mentioning
confidence: 99%